2010
DOI: 10.1136/sti.2009.040162
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual concurrency, bisexual partnerships, and HIV among Southern African men who have sex with men

Abstract: Objectives The sexual behaviour of men who have sex with men (MSM) in southern Africa has been little studied. We present here the first data on bisexual partnerships and bisexual concurrency among MSM in Malawi, Namibia and Botswana. Methods A cross-sectional probe of a convenience sample of 537 men who have ever reported anal sex with another man using a structured survey instrument and rapid-kit HIV screening. Results 34.1% of MSM were married or had a stable female partner, and 53.7% reported both male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 14 publications
14
85
1
2
Order By: Relevance
“…We used a direct measure by asking participants to report on whether they had overlapping sexual partners. While a number of other studies used similar measures [25,[41][42][43], some employed what is commonly referred to as a calendar method in which participants provide dates for the beginning and end of each sexual partnership [24,26,28,39,44,45]. Overlapping dates are then treated as concurrency.…”
Section: Discussionmentioning
confidence: 99%
“…We used a direct measure by asking participants to report on whether they had overlapping sexual partners. While a number of other studies used similar measures [25,[41][42][43], some employed what is commonly referred to as a calendar method in which participants provide dates for the beginning and end of each sexual partnership [24,26,28,39,44,45]. Overlapping dates are then treated as concurrency.…”
Section: Discussionmentioning
confidence: 99%
“…Avahan, the India AIDS Initiative funded by the Bill & Melinda Gates Foundation (19), has found that structural activities can be feasible and cost-effective, and can contribute to more sustainable HIV prevention when integrated into a package of prevention activities. Pathfi nder International, a key partner of Avahan, and its local implementing nongovernmental organization partner in Kolhapur are implementing a structural intervention that provides supported peer-led outreach, crisis response services and community mobilization to street-based sex workers, whose visibility makes them vulnerable to arrest and to violence from police, clients, and gangs (26).…”
Section: Structural Approaches To Hiv Preventionmentioning
confidence: 99%
“…Such laws contradict the commitment made by governments in the Political Declaration on HIV/AIDS in 2006 "to promote a social and legal environment that is supportive of and safe for voluntary disclosure of HIV status" (25). Countries in North America and Western Europe have long criminalized HIV transmission, and about 20 countries in sub-Saharan Africa have also chosen to do so in the past six years (26).…”
Section: Source: Mapping Of Restrictions On the Entry Stay And Residmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely held negative views about gay men and men who have sex with men in Africa, even among health care workers and academics associated with HIV care and research [73], have restricted optimal support and care for African men who have sex with men, or even research on their behalf [74][75][76][77]. Criminalization reinforces those negative views, undermines care and research, and fuels the epidemic.…”
Section: Discussionmentioning
confidence: 99%